POMONA: a multiplatform software for modeling seed physiology - Cantão, Renato Fernandes; Ribeiro-Oliveira, João Paulo; Silva, Edvaldo A. Amaral da; Santos, Amanda Rithieli dos; de Faria, Rute Quelvia; Sartori, Maria Marcia Pereira (Frontiers in Plant Science, 2023)
Seed physiology is related to functional and metabolic traits of the seed-seedling transition. In this sense, modeling the kinetics, uniformity and capacity of a seed sample plays a central role in designing strategies for trade, food, and environmental security. Thus, we are presenting POMONA (a tribute to the Roman goddess of fruit trees, gardens, and orchards), is presented as an easy-to-use multiplatform software designed to bring several logistic and linearized models into a single package, allowing for a convenient and fast assessment of seed germination and vigor (e.g., t50) or longevity (e.g., P50), even if the data has a non-Normal distribution. POMONA is implemented in JavaScript using the Quasar framework and can run in the Microsoft Windows operating system (version 10+), GNU/Linux (distribution agnostic), and Android-powered mobile hardware or on a web server as a service. The capabilities of POMONA are showcased through a series of examples with diaspores (seeds and other propagation structures) of corn and soybean, evidencing its robustness, accuracy, and performance. POMONA should can be the first step for the creation of an automatic multiplatform for that will benefit laboratory users, including those focused towards on the inclusion of image automation analysis in routine laboratories in seed science from Brazil.